Application studies on MXene-based flexible composites - Li, Pinda; Zhao, Xueling; Ding, Yaxin; Chen, Lifei; Wang, Xin; Xie, Huaqing (Frontiers in Thermal Engineering, 2024)
MXene is a novel two-dimensional layered nanomaterial with a very large specific surface area and abundant surface functional groups, endowing it with unique physical and chemical properties. MXene can be compounded with other functional materials to significantly improve the performance of MXene composites or broaden their application scope. Meanwhile, with the development of flexible composite preparation technology, it has promoted the continuous expansion of its application fields. The introduction and combination of different materials can improve the performance of flexible composites and make them have a broader application prospect. In recent years, researchers have started preparing MXene materials as flexible composites for applications such as supercapacitors, sensors, electromagnetic shielding and thermal management. This paper gives a brief introduction to flexible composites and MXene materials, reviews the applications of MXene based flexible composites in various fields as well as the research progress, and provides an outlook on their future development direction.